Analysis of Social Studies Learning Problems at SMP Negeri 23 Ambon - Rehalat, Aminah (Perspektif Pendidikan dan Keguruan, 2023)
Education is a very important thing in human life. Without education, a human being will find it difficult to adapt his life to the individual, group of individuals and his environment. Education teaches us to become individuals with character according to our potential. Education is not just about providing knowledge and making someone smarter, but it will also build character in applying the right things in our lives. Apart from that, education also functions as our investment to achieve success in the future. The aim of this research is to find out how the problems of learning Social Sciences (IPS) occur at SMP Negeri 23 Ambon. The aim of this research is to find out 1) What problems occur during the social studies learning process in the classroom. 2) Why do problems occur when social studies learning takes place? 3) How do teachers and students overcome problems that occur when learning social studies in class. The data collection technique used in this research uses a descriptive qualitative approach, namely by collecting data from teachers and students using interview, observation and documentation techniques. From the results of this research it is concluded: 1) Teachers still use the lecture learning method. 2) Lack of learning media used by teachers during social studies teaching and learning activities in class. 3) Class unconduciveness hinders teaching and learning activities